PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, EARNING PER SHARE, NET PROFIT MARGIN TERHADAP HARGA SAHAM - Erika Agustin; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This research aims to examine the influence of Current Ratio, Debt to Equity Ratio, Earning Per Share, Net Profit Margin on Stock Price. Current Ratio, Debt to Equity Ratio, Earning Per Share, Net Profit Margin as an independent variable, Stock Price as the dependent variable. This research uses secondary data with a population 44 companies, namely on Nikel sub sector mining companies listed on the Indonesia Stock Exchange in 2021-2024, 36 (thirty six) companies are the research sample with the observation year 2021-2024. The sampling technique used was purposive sampling with the multiple linear regression analysis method. The results of the research show that simultaneously Current Ratio, Debt to Equity Ratio, Earning Per Share, Net Profit Margin influences Stock Price. Partially, Current Ratio and Debt to Equity Ratio have a positive influences Stock Prices, Earning Per Share has a negative influences Stock Price, while Net Profit Margin have no effect on Stock Prices